Avaliação das facetas dos cinco grandes fatores de personalidade: construção de um instrumento de medida - Palhano, Dandara Barbosa (2016)
Usually, the people are well understood by somebody else, considering adjectives who describe their behaviour. This description or characterization is consider a singularity of these personality under your pairs. Some theoretical share the idea that traits are fundamental units of personality, presenting a high range of dispositions for answer the questions in certain ways. Therefore, the personality is a construct which strong influence under the behaviours, with influence in behaviours associate to healthy too. The Five Big Factors Associated with the Personality is considered a model well understood and with great replicability in many countries, who subsidized the formulation of instruments for personality rating. Taking this big concept for make a psicological evaluation, is necessary to use instruments that are not too long and whose items are easily understand by the subjects evaluated. Considering this needs and the importance of personality evaluation, the goal of this study was development and get evidences valid for a construct of a instrument for personality evaluation. Comparisons were made between two types of scale, one based on the Likert method and the other on the semantic differential method and another in differential semantic method. The research was count with a living togheter sample of 247 people in the Pilot Study and 571 attendees in the Final Study, of the both sexes and college students. The scales passed through semantic analysis with 10 subjects of lower extract of the population. It was also carried out the analysis of judges with three experts. In the Final Study were held 7 Factor Analyses (AF) for each scale, was also calculated Cronbach's alpha for each facet and dimensions in order to verify the reliability of the instruments. From the found psychometric results, it opted for the Semantic Differential scale to perform the analyzes of the items by the Item Response Theory. Therefore, the Semantic Differential Scale presented construct evidence of construct validity of as well as evidence of accuracy, be appropriate for personality evaluation.